THE BENEFIT OF COUNSELLING TO PREGNANT WOMEN WITH A HISTORY OF SPONTANEOUS ABORTION: A CASE REPORT - Qatrunnada Naqiyyah Khusmitha (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Background: Abortion becomes a complication that can occur in pregnancy and cause psychological and physical distress. Spontaneous abortion can become trigger anxiety and depression during pregnancy. Midwifery who helps patients in perifer or rural areas need to concern about how to do early detection and counseling to reduce risk of psychological risk which can be elevated.Objective: This report aimed to evaluate the anxiety and depression state with a history of spontaneous abortion in their first pregnancy.Methods: This paper was a case report reporting a patient with a second pregnant condition. This patient has a history of spontaneous abortion in her first pregnancy. Evaluating process with Hamilton Anxiety Rating Scale (HAM-A) dan Hamilton Depression Rating Scale (HDRS) and follow-up after parturition period.Results: Decreasing scores on HAM-A and HAM-D after counseling helped the patient to release her anxiety and depression duringpregnancy. The patient is more prepared about signs and symptoms when she feels uneasy and overwhelmed and protects herself from another distortion cognition from spontaneous abortion.Conclusion: Counselling had benefits to decrease anxiety and depression in pregnant women with a history of spontaneous abortion. Keywords: anxiety, depression, spontaneous abortion.